Perception of Urban Slum in Lagos and Correlation Between Lack of Education and Causes of Violence and Crime: Open and Distance Learning (ODL) as Panacea - Adegoke, Niyi (West African Journal of Open and Flexible Learning, 2017)
Globally, the improvement in the information and communication technology and the need to educate majority of population brought about a new mode of teaching and learning: Open and Distance Learning has been made to cover unreachable set of people by exposing and enlightening their mind and generally, contribution to all levels of development. The aim of this study is to examine the possible role of Open and Distance Learning (ODL) in curbing violence and crime in Urban Slum areas in Nigeria. The study adopted survey research method. The objectives of the study to examine urban slum people’s perceptions of ODL, to ascertain perception of the causes of crime and violence in urban slum, to analysis the correlate between ODL and crime and violence. A sample size of 250 respondents was drawn. The finding revealed that people’s perception of open and distance system condones laziness, it’s for workers, adults and certificate is unemployable was wrong and not right. The study therefore recommends that the government should invest heavily on ODL since it creates knowledge, enlightenment and power which turn reduces crime and violence. Résumé : Au niveau mondial, l’amélioration des technologies de l’information et de la communication et la nécessité d’éduquer la majorité de la population ont créé un nouveau mode d’enseignement et d’apprentissage : l’apprentissage ouvert et à distance a été créé pour couvrir un ensemble inaccessible de personnes en exposant et en éclairant leur esprit, et en général, contribution à tous les niveaux de développement. Le but de cette étude est d’examiner le rôle possible de l’apprentissage ouvert et à distance dans la lutte contre la violence et la criminalité dans les bidonvilles urbains du Nigeria. L’étude a adopté une méthode de recherche par sondage. Les objectifs de l’étude étaient d’examiner les perceptions des personnes vivant dans des bidonvilles dans les bidonvilles urbains, de déterminer leur perception des causes de la criminalité et de la violence dans les bidonvilles urbains et d’analyser la corrélation entre ODL, crime et violence. Un échantillon de 250 répondants a été tiré. La découverte a révélé que la perception du système ouvert et éloigné par les gens tolère la paresse, c’est pour les travailleurs, les adultes et que le certificat est inemployable. L’étude recommande donc que le gouvernement investisse lourdement dans l’ODL, dans la mesure où il crée des connaissances, des connaissances et un pouvoir qui, à leur tour, réduisent la criminalité et la violence.